THE INFLUENCE OF KNOWLEDGE MANAGEMENT ON ORGANIZATIONAL PERFORMANCE WITH ERP IMPLEMENTATION AS MEDIATOR - Muhammad Ramdani, Derri; Hady Siti Hadijah (Dinasti Publisher, 2020)
This study examines whether knowledge sharing has influence on organizational performance, where Enterprise Resource Planning (ERP) is used as a mediator connecting these two variables. ERP system is unique because it requires users who have more knowledge and have special skills, in contrast to usual users who usually do their job manually. In corporation world, an integrated system like ERP should be well-socialized at maximum rate to reach performance effectiveness and efficiency that will surely result in organizational productivity. Nonetheless, in many organizational cases there are still numerous employees who decline to share knowledge in regeneration process due to their fears of being replaced by younger ones and this keeps the knowledge sharing process on hold. With total of 500 employees in a textile company in Bandung County, the writer takes 250 samples as the population representation. Data analysis is undergone through Structure Equating Model (SEM) with assistance of SPSS application, the writer can see the relationship of knowledge sharing and its influence on organizational performance.